Pengaruh Biaya Lingkungan Dan Pengungkapan Lingkungan Terhadap Nilai Perusahaan Dengan Dewan Komisaris Independen Sebagai Pemoderasi - Regina Theresia Eku; Hasnawati Hasnawati (Journal of Creative Student Research, 2024)
This research was conducted because researchers wanted to know the influence of environmental costs, environmental disclosure and environmental performance on company value with an independent board of commissioners as moderator in manufacturing companies in Indonesia during the period 2021 to 2022. This research is a replication of Hidayat et al's research. al., (2023) "The Effects of Environmental Cost, Environmental Disclosure and Environmental Performance on Company Value with Independent Board of Commissioners as Moderation" in research conducted on the Indonesia Stock Exchange in 2018-2021, and to measure the independent board of commissioners using the formula the number of independent commissioners is divided by the number of independent commissioner board members multiplied by 100%, while the research to be carried out by the author will be carried out on the Indonesia Stock Exchange in 2021-2022 and will take a sample of all Basic Materials companies in the Raw Goods sector and Industrial companies ( Industrials) Industrial Goods sector listed on the Indonesian Stock Exchange, and to measure the independent board of commissioners using the formula for the number of meetings of the board of commissioners in one year.